Epidemiological profile of infections by COVID-19 in the city of Parnaíba-PI (Research, Society and Development, 2021)
Introduction: The behavior of the COVID-19 pandemic results from several factors, such as viral and population characteristics and the use of measures to control the number of cases. The variety of such factors in each territory is responsible for creating unique epidemiological profiles, the study of these profiles is essential to understand the behavior of the epidemic and plan measures to fight the disease. To this end, the current study proposes to investigate the profile of infections by the new coronavirus in the city of Parnaíba-PI. Objective: To trace the epidemiological profile of SARS-CoV-2 infections in the city of Parnaíba-PI. Methods: This is a secondary descriptive epidemiological study, which used data collected through the COVID-19 case notification form, between March 2020 and 2021, the cases whose cases were not included in the analysis. data in the notification forms were incomplete. Results: The analysis included 11,864 cases diagnosed in the period. Conclusion: The cases analyzed consisted mainly of women, and were mainly in age groups from 20 to 59 years, with a peak incidence in the range from 30 to 39 years. The vast majority did not report comorbidities or risk situations. The most reported symptoms were fever, cough and sore throat.